2019
DOI: 10.1080/14737175.2019.1623671
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage: an update on diagnosis and treatment

Abstract: Introduction: Spontaneous nontraumatic intracerebral hemorrhage (ICH) is most often caused by small vessel diseases: hypertensive arteriopathy or cerebral amyloid angiopathy (CAA). Although ICH accounts for only 10-15% of all strokes it causes a high proportion of stroke mortality and morbidity, with few proven effective acute or preventive treatments. Areas covered: We conducted a literature search on etiology, diagnosis, treatment, management and current clinical trials in sICH. In this review we describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
162
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(169 citation statements)
references
References 180 publications
(145 reference statements)
0
162
1
6
Order By: Relevance
“…The expression levels of genes of interest, which encode hemoglobin, Na+/H+ exchanger, and carbonic anhydrase, were verified by real-time PCR analysis. Hemoglobin proteins caused dramatic neuronal toxicity in cerebral hemorrhage and regulated the oxygen and carbon dioxide exchange with carbonic anhydrase in blood cells ( Hostettler et al, 2019 ; Nikinmaa et al, 2019 ). We found that the mRNA expression levels of hemoglobin ( hbae1.3, hbae3, hbae5, hbbe2 and hbbe3 ), Na+/H+ exchanger ( slc4a1a and slc9a1 ), and carbonic anhydrase ( cahz ) genes were significantly elevated after cerebral hemorrhage, while STS alleviated the expression changes in of these genes ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of genes of interest, which encode hemoglobin, Na+/H+ exchanger, and carbonic anhydrase, were verified by real-time PCR analysis. Hemoglobin proteins caused dramatic neuronal toxicity in cerebral hemorrhage and regulated the oxygen and carbon dioxide exchange with carbonic anhydrase in blood cells ( Hostettler et al, 2019 ; Nikinmaa et al, 2019 ). We found that the mRNA expression levels of hemoglobin ( hbae1.3, hbae3, hbae5, hbbe2 and hbbe3 ), Na+/H+ exchanger ( slc4a1a and slc9a1 ), and carbonic anhydrase ( cahz ) genes were significantly elevated after cerebral hemorrhage, while STS alleviated the expression changes in of these genes ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis and pathophysiology underlying ICH are complex. The space-occupying effect of the hematoma along with blood infiltration into the brain parenchyma could trigger multiple cellular and molecular responses around and beyond the lesion site, such as ischemia, blood-brain barrier disruption, oxidative stress and neuroinflammation, which may result in acute and chronic neuronal damage and neurological dysfunction [8,12,15]. Clinical trials suggest that vasospasm of larger brain vessels is not the sole contributor to neurological outcome, and intense efforts have been turned to mechanisms of early brain injury that may play a larger role in functional outcome, including neuroinflammation and microvascular dysfunction [47].…”
Section: Discussionmentioning
confidence: 99%
“…Much progress has been made in recent years in understanding the pathogenesis of ICH [7,10]. However, unfortunately, none of the current clinical interventions, including aggressive blood pressure control, homeostasis management and platelet transfusion, have significantly improved the outcome of cerebral stroke among patients [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…I ntracranial haemorrhage (ICH) as a common stroke subtype, caused by blood leaking into the brain parenchyma. This critical neurologic injury is responsible for 10-20% of strokes [1][2][3][4][5]. ICH comprises four different types: epidural and subdural hematoma, intracerebral haemorrhage, and subarachnoid haemorrhage (SAH).…”
Section: Introductionmentioning
confidence: 99%